KONSEP KEBAHAGIAAN SEJATI DARI PERSPEKTIF STOISISME DALAM FILM SEPATU DAHLAN: (KAJIAN SEMIOTIKA) - Septiani, Rifanny Zahra; Syihabuddin, Syihabuddin (ESTETIKA: JURNAL PENDIDIKAN BAHASA DAN SASTRA INDONESIA, 2023)
This paper analyzes the concept of true happiness in the film "Sepatu Dahlan" from the perspective of stoicism philosophy. The purpose of this paper is to find out how this film defines true happiness and to analyze the depiction of the actions of the characters in the film to achieve true happiness. This paper uses qualitative methods with semiotic analysis from Ferdinand De Saussure. To analyze the data, this study uses the philosophical theory of stoicism in the book Terrace Philosophy by Henry Manampiring which is based on the thoughts of stoic philosophers such as Seneca, Epictetus, and Emperor Marcus Aurelius. The research findings show that this film defines true happiness through the actions of the characters in the film which are driven by the dichotomy of control, namely aspects that we can control to achieve true happiness, living free from negative emotions and living full of virtues: wisdom, justice, courage, restraint. A life free from negative emotions is depicted when the character can control himself not to feel sad, angry, worried and disappointed when facing the events that befall him in his life. A virtuous life is described when the character can use his reason or rationality well.